Urine cortisol in pigs of different MH-genotypes - Nataša SIARD; Milena KOVAČ; Jan LADEWIG; Ivan ŠTUHEC (Acta Agriculturae Slovenica, 2003)
Urine cortisol concentration was evaluated in German Landrace barrows of two MH-genotypes (NN, Nn) housed in metabolic cages. Furthermore, cortisol in urine was evaluated as a substitute measure of plasma cortisol values in pigs. Three replicates were done, each including 4 animals. Altogether there were 12 animals included in the experiment. The effect of MH-genotype on urine cortisol concentration was evaluated and correlations between urine and plasma cortisol were calculated. Higher urine cortisol values in NN- in comparison to Nn-pigs indicated stronger response to stressors by stress resistant NN-genotype. The correlation between urine (12-hr urine values) and plasma (the average of 12 collections per day, taken between 8.00 a.m. and 11.00 a.m.) cortisol values was practically negligible in samples taken on the same day (r = 0.07, P = 0.71). In time-lag samples (urine taken the day after blood collection) correlation was increased (r = 0.22), but still not significant (P = 0.22). A connection between plasma and urine cortisol values was indicated, but it should be better understood before urine cortisol is used as a substitute of plasma cortisol measuring in pigs.